2012
DOI: 10.1590/s0080-62342012000600017
|View full text |Cite
|
Sign up to set email alerts
|

Idosos vítimas de trauma: análise de fatores de risco

Abstract: RESUmoO objetivo deste estudo foi identificar fatores de risco para o trauma em idosos a partir de abordagem quantitativa e transversal, utilizando análise de regressão logística. Foi realizado no pronto-socorro de dois hospitais da cidade de Curitiba-PR. Foram entrevistados 261 idosos, sendo 56,7% mulheres e 43,3% homens. A idade variou de 60 a 103 anos, com maior concentração em idosos menores de 70 anos (44,8%). Os mecanismos de trauma mais frequentes foram: queda (75,9%), atropelamento (9,6%), trauma diret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
1
9
0
13
Order By: Relevance
“…This could be explained by the anatomical, physiological, immunological and hormonal differences which play an important role in the gender-specific trauma outcome. In almost all types and mechanism of injuries, the frequency of male gender is disproportionately high and masks the impact of trauma in female population [90,91]. Further research should emphasize the main causes of Injury, differences in treatment, complications, and long term outcomes among females.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the anatomical, physiological, immunological and hormonal differences which play an important role in the gender-specific trauma outcome. In almost all types and mechanism of injuries, the frequency of male gender is disproportionately high and masks the impact of trauma in female population [90,91]. Further research should emphasize the main causes of Injury, differences in treatment, complications, and long term outcomes among females.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Roberts & Ciosak 29 showed that elderly persons who took medication over a continuous period were more likely to fall. In the present study, drugs, which have been found in some studies to be an important risk factor for falls, were not divided by class (anxiolytics, antihypertensives, diuretics).…”
mentioning
confidence: 99%
“…As consequências podem ser leves ou graves, gerando elevado custo para a sociedade (gastos com hospitalização, tratamento e reabilitação), além de custos significativos para a família. 2,16 Quanto à presença de atendimento pré-hospitalar, exatamente a metade dos pacientes recebeu esse tipo de suporte, entretanto 52,6% dos idosos vítimas de queda da própria estatura não receberam esse atendimento inicial, buscando por conta própria o serviço de emergência. Muitos idosos ignoram a importância da ocorrência de quedas, por acreditarem que estas são inerentes ao envelhecimento.…”
Section: Discussionunclassified